SINERGI PROFESIONALISME GURU DALAM MEMAJUKAN MUTU PENDIDIKAN DI ERA KEPEMIMPINAN KEPALA SEKOLAH DAN MERDEKA BELAJAR : STUDI KASUS SD MUHAMMADIYAH PATI - Ana Nur Aini; Anam Sutopo; Sofyan Anif (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to explore the collaboration between principal leadership and teacher professionalism in improving the quality of education in the Merdeka Belajar era at the elementary school level. The basis of this research is the persistent gap between the expectations of national education policy and actual implementation in the field, particularly regarding the role of the principal and teacher professional skills. This research used a qualitative approach with a descriptive case study method at Muhammadiyah Elementary School in Pati, which has successfully implemented the collaborative principle. Data collection methods included participant observation, semi-structured interviews, and documentation analysis. The research findings indicate that transformational, collaborative, and visionary principal leadership can foster teacher professionalism through strengthening learning communities, ongoing training, and reflective communication. Effective collaboration contributes significantly to improving the quality of education, as evidenced by teacher enthusiasm, innovation in teaching, and improved student learning outcomes. This study emphasizes the importance of integrating innovative leadership styles and teacher professional development as a foundation for achieving the Merdeka Belajar goals. Practical and policy recommendations are proposed to strengthen the development of learning communities and the principal's role as a learning leader.